1985
DOI: 10.1002/j.1460-2075.1985.tb03922.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of two forms of the interferon-induced (2′-5′) oligo A synthetase of human cells based on cDNAs and gene sequences.

Abstract: The (2′‐5′) oligo A synthetase E, one of the translational inhibitory enzymes whose synthesis is strongly induced by all interferons (IFNs), is shown to be encoded in human cells by a 13.5‐kb gene. By a cell‐specific differential splicing, between the seventh and an additional eighth exon of this gene, two active E mRNAs of 1.6 and 1.8 kb are produced, along with several longer transcripts. cDNA clones for the two mRNAs were obtained and their sequences indicate that the human (2′‐5′) oligo A synthetase gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
94
0
2

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(102 citation statements)
references
References 64 publications
6
94
0
2
Order By: Relevance
“…The two types of IFNs differ, however, notably in their structure, their cell surface receptors, and their biological activities [2,3]. It is therefore logical that the characteristics of induction of the cloned 2-SA synthetase mRNAs [4] by the two IFNs are not similar [5,6]. The mRNAs are induced much less by IFNy than by type I IFNs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The two types of IFNs differ, however, notably in their structure, their cell surface receptors, and their biological activities [2,3]. It is therefore logical that the characteristics of induction of the cloned 2-SA synthetase mRNAs [4] by the two IFNs are not similar [5,6]. The mRNAs are induced much less by IFNy than by type I IFNs [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The activated nuclease hydrolyses mRNA and therefore protein synthesis is inhibited in interferon-treated cells (Kerr & Brown, 1978;Slattery et al, 1979). Oligo-2',5'-adenylate synthetase (2-5AS) has been fully characterized and its gene has been cloned (Benech et al, 1985;Merlin et al, 1983). It is therefore now possible to use a plasmid with sequences from the 2-5AS gene to study directly the levels of its expression in control, virus-infected or interferon-treated cells.…”
mentioning
confidence: 99%
“…In that way interferons, as other cytokines, act as pleiotropic effectors, since they modify not only the biochemistry of some target cells but also the physiology of the entire organism. Conversely it has been suggested that some other cytokines (tumor necrosis factors c( and p [3,41) have intrinsic antiviral activities.Numerous cDNAs corresponding to interferon-inducible genes have been cloned but the biological function of these genes has been discovered in a few cases only. Their transcriptional regulation appears to be rather complex.…”
mentioning
confidence: 99%
“…Beside the establishment of an antiviral state, interaction between interferon and its receptor on the cell surface also leads to a wide range of biological effects, such as the inhibition of cell growth and modulations of the immune system (for reviews see [l, 21. In that way interferons, as other cytokines, act as pleiotropic effectors, since they modify not only the biochemistry of some target cells but also the physiology of the entire organism. Conversely it has been suggested that some other cytokines (tumor necrosis factors c( and p [3,41) have intrinsic antiviral activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation